Familiarity reduces aggression but does not modify acoustic communication in pairs of Nile tilapia (Oreochromis niloticus) and black‐chinned tilapia (Sarotherodon melanotheron). Issue 2 (15th December 2021) - Akian, Dieudonné Djétouan; Yao, Kouakou; Parmentier, Eric; Clota, Frédéric; Baroiller, Jean‐François; Bégout, Marie‐Laure
Abstract: Reproduction involves multiple complex behaviours, and the effects of familiarity on such social interactions are seldom described in fish. This is particularly true for sound production and communication within aggressive or non‐aggressive context. This study explores the effects of a common garden rearing without parental care of two closely related cichlid species (Nile tilapia Oreochromis niloticus and black‐chinned tilapia Sarotherodon melanotheron ) on their sound production features and social interactions. After 9 months in common garden rearing, from embryonic stage to first maturity, sound production and associated behaviours were recorded on specimens of the two species in intraspecific and interspecific pairings. The authors found that fish were able to produce the same kind of sounds as those recorded in similar context for their parents. Drum sounds were associated to chasing, lateral attack and courtship in O. niloticus and only to fleeing or avoidance in S. melanotheron . Specific grunts were produced in chasing, after biting and in nest building by O. niloticus, and specific rolling sounds were associated to courtship in S. melanotheron . Sound production and behaviours were not correlated to sex steroid levels, but the number of sounds recorded in aggressive context was correlated to dominance in O. niloticus . The authors conclude that one generation of common garden rearing does not modify sound features, which remain specific and innate in the two cichlids. Despite the familiarity, O. niloticus remained dominant on S. melanotheron, but the aggressiveness between the two species decreased.